Bandwidth Enhancement of Microstrip Antenna for Wireless Local Area Network Applications - Doraisingam, Yoharaaj (2007)
These days, there is a very large demand for wireless applications. Antennas which are used in these applications should be low profile, light weight, low volume and broad bandwidth. The microstrip antenna suits the features mentioned except for its narrow bandwidth, typically ranges from less than one percent to several percent of relative bandwidth. By reducing that limitation, the advantages using microstrip antenna can further outweigh its disadvantages. In this research, an alternative bandwidth enhancement technique is studied and then proposed in order to broaden the bandwidth of the microstrip antenna. The wireless application that is selected to be studied is the Wireless Local Area Network (WLAN) based on the IEEE 802.11b standard. In Malaysia, this WLAN band spans from 2.4GHz to 2.5GHz.